WHEN WORK AND FAMILY COLLIDE: CAN JOB SATISFACTION PREVENT BURNOUT IN FEMALE MPLOYEES? - Mohammad Bukhori; Fathorrahman Fathorrahman; Mohammad Nailur Rochman (Jurnal Apresiasi Ekonomi, 2026)
Female employees frequently face challenges in balancing work roles and family responsibilities, which can trigger work-family conflict (WFC). The phenomenon of women working in banks as a career choice is very common, and they often experience conflict between fulfilling their duties as employees and performing their duties as housewives, taking care of their children. Research findings regarding the role of job satisfaction as a mediator in this relationship still show mixed results. This inconsistency indicates a research gap that needs further exploration, particularly in the context of female employees. Therefore, this study aims to examine the role of job satisfaction in mediating the influence of work-family conflict on burnout in female employees. Using simple random selection, the study's sample of 100 respondents is made up of female bank employees in the city of Pasuruan. Questionnaires were given to respondents in order to collect data, and SEM-PLS was used to analyze the results. The research findings indicate that first, work-family conflict has a significant positive effect on burnout and job satisfaction. Second, job satisfaction also has a significant positive effect on burnout. Third, job satisfaction serves as a mediating variable for the impact of work-family conflict on burnout. Keyword : Work_Family_Conflict; Burnout; Job_Satisfaction; Female_Employees